Efficiency of Plating on Chick Embryo Cells and Kinetic Neutralization of Herpesvirus hominis Strains - Wentworth, Berttina B. (1972)
Since it appeared that plaque formation in monolayers of primary chick embryo cells might provide a simple technique for the typing of Herpesvirus hominis strains, 100 isolates were tested for their efficiency of plating (EOP) on chick embryo cells versus plating on human embryonic fibroblasts. EOP values varied from 10(0) to 10(−6): 88% of the strains of genital origin had an EOP equal to or greater than 10(−2), and 82% of the oral isolates had an EOP equal to or less than 10(−3). Kinetic neutralizations were done with 53 strains, including those 12 with an EOP of 10(−2) or 10(−3). An estimate of antigenic relatedness (R(a)) between strains was calculated from the neutralization results. Although the site of recovery, EOP, and R(a) generally correlated, the EOP of some oral strains did not agree with the neutralization results, and some genital strains showed type 1 EOP and R(a) values. Selection of variants with increased EOP values did not result in accompanying changes in R(a). Thus, the two markers appeared to vary independently. These data support other findings which suggest that there may be no absolute correlation between biological and antigenic markers in herpesviruses and that a larger number with more diversity of strains should be examined for more markers before a typing system is established.